The association of Leptospermum honey with cytokine expression in the sinonasal epithelium of chronic rhinosinusitis patients. Issue 1 (1st March 2019) - Manji, Jamil; Thamboo, Andrew; Sunkaraneni, Vishnu; Singh, Amrit; Tebbutt, Scott; Garnis, Cathie; Javer, Amin
Abstract : Objective: To identify the differences in cytokine expression between sinonasal tissue from patients treated with Leptospermum (Manuka) honey (LH) irrigation versus normal saline irrigation twice‐daily for twelve weeks following sinus surgery (FESS). Methods: Forty‐six CRS patients were recruited. Sinus tissue biopsies were collected during FESS and then at 5 and 12 weeks postoperatively during the course of treatment. A multi‐plex cytokine assay quantified the abundance of 17 cytokines in biopsied tissue. Cytokine expression fold‐change was analyzed between each time point using a robust linear regression model and compared between the two treatment groups. Results: Compared to the saline irrigation group, five cytokines were differently expressed ( CI = 95%) in sinonasal tissue obtained from subjects in the LH irrigation group during the 12‐week treatment period. Cytokines IL‐6 ( P = 0.0400), IL‐8 ( P = 0.0398), MCP‐1 ( P = 0.0284), and MIP‐1β ( P = 0.016) were significantly increased in the LH irrigation group compared to the saline irrigation group. IL‐13 was significantly increased in the saline irrigation group compared to the LH group ( P = 0.0086). Conclusion: LH may potentially act to modulate the expression of IL‐6, IL‐8, IL‐13, MCP‐1 and MIP‐1β in sinonasal tissue.